Long-Term Sustainability of Outer Space: Role of Sustainable Development Goals and Its Legal Consequences - Kumar, Vijay; Raju, K D; Subramanian, S R (Universitas Negeri Semarang, 2023)
Celestial phenomena have historically contributed to natural processes, but their collision paths and debris generation have increasingly threatened outer space. Human activities in space exacerbate these risks, prompting concerns over the preservation of the space environment. The United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS) has responded by initiating sustainable space initiatives. In 2010, UNCOPUOS's Scientific and Technical Subcommittee established a Working Group on the Long-Term Sustainability of Outer Space Activities. This group aims to develop voluntary guidelines for states, international organizations, and private entities to ensure sustainable space practices. The collaboration between Avio, an Italian aerospace company, and the United Nations Office for Outer Space Affairs (UNOOSA), forged during the 74th Session of the United Nations General Assembly in September 2019, is a notable step towards enhancing space accessibility, particularly for developing nations. This paper examines various aspects of sustainable space practices, including their alignment with the Sustainable Development Goals (SDGs). Part one introduces sustainable development principles and the global imperative for environmental protection. Part two explores the role of space technologies in advancing the SDGs. Part three investigates whether the SDGs encompass space-related objectives and proposes strategies for achieving sustainable space practices. Finally, part four advocates for a robust regulatory framework for sustainable space activities, emphasizing the need to learn from past environmental mistakes and protect the integrity of outer space.